Effect of growth differentiation factor-9 and fibroblast growth factor-basic on small caprine oocyte development in vitro - GUPTA, P S P; SHREE, US PAVANNA; DHALI, A; NANDI, S (The Indian Journal of Animal Sciences, 2018)
The study aimed to assess the effect of growth differentiation factor-9 (GDF-9) and fibroblast growth factorbasic (bFGF) on in vitro development of small (<126 μm diameter) caprine oocytes. Small oocytes were recovered from abattoir derived caprine ovaries and matured in vitro (24 h) in the presence of GDF-9 (0, 10, 20, 30 ng/ml) or bFGF (0, 10, 20, 30 ng/ml), and maturity and viability rates were assessed. A combination of both the growth factors (GDF-9, 30 ng/ml + bFGF, 20 ng/ml) was used to mature the oocytes in vitro (24 h). Subsequently oocytes were fertilized in vitro with cauda epidydimis sperm processed with BO medium (2×106/ml sperm). Cleavage and fertilization rates were assessed at 42 to 48 h post-insemination and morula/ blastocyst rate was assessed on 7 to 8 d post-fertilization. Maturation rate was significantly greater in oocytes cultured in media containing 30 ng/ml GDF-9 or 20 ng/ml bFGF compared to control. Maturation, fertilization, cleavage and morulae/blastocyst rates were significantly greater in oocytes cultured in combination of GDF-9 and bFGF compared to control. In conclusion, the supplementation of GDF-9 and bFGF in in vitro maturation (IVM) medium improved the maturation rate and embryo development of small caprine oocytes.